Ricostituzione Funzionale in Liposomi del Trasportatore Glutammina-Amminoacidi Neutri, B°-like, di Rene di Ratto - Oppedisano,Francesca; Pochini,Lorena; Canonaco,Marcello (My University, 2013)
In this work we have studied the functional properties of amino acid transporters using liposomes reconstituted with solubilized renal brush borders. Among the numerous amino acid transport systems of the plasma membrane, there is a restricted group of transporters that share the specificity for glutamine. In mammals, these transporters play the important function of mediating glutamine trafficking among different tissues and intestinal and renal (re)absorption. In the last decade the genes coding for the glutamine-specific transport systems have been identified and the encoded proteins have been characterized in expressing cell systems. A general feature of the proteins that mediate glutamine transport is the more or less broad specificity towards different amino acids: thus, the glutamine transporters are also designated as amino acid transporters with specificity towards glutamine. The various transporters can be assigned to different protein families on the basis of their structural features. The glutamine specific transporters can be functionally divided in two groups: sodiumdependent (systems ASCT2/ATB0, N, B0,+, A and y+L) and sodium-independent (systems L and b0,+) transporters. Among the sodium-dependent transporters, a further distinctive feature is the high (N and y+L) or low (ASCT2) tolerance towards the substitution of Na+ by Li+. In general, the transporters are characterized by the different specificity for amino acids and sensitivity to inhibitors; for example, the amino acid analogue MeAIB is used to assess the function of System A. More recently another sodium-dependent amino acid transporter which is also specific for glutamine has been identified: B0AT1. This transport system, which belongs to the SLC6 transporter family, is highly expressed in mouse kidney and is specific for all the neutral amino acids, which are cotransported with sodium. B0AT1 corresponds to the transport system, previously found in bovine renal epithelial cells, named B0. Mutations of the B0AT1 Abstract 6 gene (SLC6A19) cause the Hartnup disorder. In spite of the very large amount of experimental data deriving from the studies on the glutamine transporters, several aspects of the transporter function and regulation are still unclear or unraveled. The procedure of reconstitution into liposomes has often been helpful in clarifying functional properties of membrane transport systems since it allows some types of experiments that cannot be accurately performed in cell systems. In the present study a procedure has been pointed out for efficient reconstitution in liposomes of a rat kidney transport system which is specific for glutamine and neutral amino acids. The reconstituted system was optimised with respect to the critical parameters of the cyclic detergent removal procedure, i.e., the detergent used for the solubilization, the protein concentration, the detergent/phospholipid ratio and the number of passages through a single Amberlite column. In the reconstituted system, the transporter showed all the basic functional properties of B0AT1; thus, it has been classified as B0-like. Novel functional aspects of the transporter have been revealed. Time dependent [3H]-glutamine accumulation in proteoliposomes occurred only in the presence of external Na+ and internal K+. The transporter showed low if there is any tolerance towards the substitution of Na+ or K+ for other cations. Valinomycin strongly stimulated the transport indicating that it is electrogenic. Intraliposomal glutamine had no effect. From the dependence of the transport rate on the Na+ concentration cooperativity index close to 1 was derived, indicating that 1 Na+ should be involved in the cotransport with glutamine. The electrogenicity of the transport originated from the Na+ co-transport. Optimal rate of 0.1 mM [3H]-glutamine uptake was found in the presence of 50 mM intraliposomal K-gluconate. At higher K-gluconate concentrations the transport rate decreased. The activity of the reconstituted transporter was pH dependent with optimal Abstract 7 function in the range pH 6.5–7.0. [3H]-glutamine (and [3H]-leucine) uptake was inhibited by all the neutral but not by the positively or negatively charged amino acids. The sulfhydryl reagents HgCl2, mersalyl, p-hydroxymercuribenzoate and the substrate analogue 2-aminobicyclo[2,2,1] heptane-2-carboxylate strongly inhibited the transporter, whereas the amino acid analogue a-(methylamino)isobutyrate had no effect. The inhibition by mersalyl was protected by the presence of the substrate. The dependence of the transport rate on internal glutamine concentration was measured; the Km value of the transporter for internal glutamine is 2.01 ± 0.4 mM. The transporter is functionally asymmetrical and it is unidirectionally inserted into the proteoliposomal membrane with an orientation corresponding to that of the native membrane. By a bisubstrate kinetic analysis of the glutamine uniport, a random simultaneous mechanism of transport was found. The physiological role of the dependence on internal (intracellular) K+ of the B0-like transporter may be related with the signaling of the metabolic condition of the cell. The intracellular concentration of K+ is influenced by a complex regulation of apical K+ channel in kidney, which are activated at sub-millimolar and inhibited at higher (millimolar) ATP concentration. Consequently, the intracellular K+ concentration will decrease or increase, respectively, at lower or higher ATP level. Thus, K+ may modulate the activity of the B°-like transporter in response to the level of ATP. Modulation by ATP was previously found for the reconstituted ASCT2, which is directly stimulated by higher intracellular ATP level (Oppedisano et al 2004, 2007). Since B0AT1 and ASCT2 mediate uniport or antiport of neutral amino acids, respectively, the complex mechanism of modulation of their activity will regulate the balance between net uptake and exchange of amino acids in response to the metabolic state of the cell. Abstract 8 This cross-talk between B0AT1 and ASCT2 together with the peculiar specificity of ASCT2 towards glutamate support the occurrence and the modulation of the tertiary active transport recently proposed by Broer, involving the antiport of external glutamate with internal neutral amino acids mediated by ASCT2, followed by reuptake of the neutral amino acids by B0AT1 (Oppedisano and Indiveri 2008).
Dottorato di Ricerca in Biologia Animale, Ciclo XXII, SSD BIO/10, a.a.2008-2009
Keywords: Biologia animale; Lipoma; Ratto